2008
DOI: 10.1007/s00221-008-1329-5
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory postural adaptations during continuous, variable amplitude perturbations reveal generalized rather than sequence-specific learning

Abstract: We examined changes in the motor organization of postural control in response to continuous, variable amplitude oscillations evoked by a translating platform and explored whether these changes reflected implicit sequence learning. The platform underwent random amplitude (maximum ± 15 cm) and constant frequency (0.5 Hz) oscillations. Each trial was composed of three 15-second segments containing seemingly random oscillations. Unbeknownst to participants, the middle segment was repeated in each of 42 trials on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 26 publications
(23 reference statements)
4
77
0
2
Order By: Relevance
“…This limitation of transfer, i.e., the specificity of the acquired task solution routine, not only to its physical parameters, but perhaps also to its context, is in agreement with previous studies (Keetch et al, 2008;Keshner et al, 2004;Korman et al, 2003;Karni et al 1998). The decrease in the CoP displacements in response to the structured perturbations in the perturbation tests was apparent in both groups and thus can be ascribed to the repeated experience of the perturbations during the 5 tests (time-points) (Van Ooteghem et al, 2008). This pattern of results is in line with learning in the Finger Opposition Sequence task, wherein the gains were consistently found to depend on the order of the trained sequence (Rozanov et al, 2010;Korman et al, 2003;Karni et al 1998), as well as with skill learning in more complex tasks (Keetch et al, 2008;Keshner et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This limitation of transfer, i.e., the specificity of the acquired task solution routine, not only to its physical parameters, but perhaps also to its context, is in agreement with previous studies (Keetch et al, 2008;Keshner et al, 2004;Korman et al, 2003;Karni et al 1998). The decrease in the CoP displacements in response to the structured perturbations in the perturbation tests was apparent in both groups and thus can be ascribed to the repeated experience of the perturbations during the 5 tests (time-points) (Van Ooteghem et al, 2008). This pattern of results is in line with learning in the Finger Opposition Sequence task, wherein the gains were consistently found to depend on the order of the trained sequence (Rozanov et al, 2010;Korman et al, 2003;Karni et al 1998), as well as with skill learning in more complex tasks (Keetch et al, 2008;Keshner et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…It is also clear that the repeated (5 sessions) testing afforded in the perturbation tests (transfer conditions) led to a significant reduction in sway in both the training and the control groups. Reductions in sway may characterize the coping of young healthy adults with repeated patterns of balance perturbations (Van Ooteghem et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To substantiate whether learning a repeated waveform pattern could still occur when the between-segment tracking complexity was controlled for, Chambaron et al replicated Wulf and Schmidt (1997), but had each participant track a different repeated waveform pattern. They found that tracking of the repeated pattern was no more accurate than for the random patterns (see also van Ooteghem, Frank, Allard, Buchanan, Oates, & Horak, 2008 A second methodological issue associated with the continuous tracking task paradigm was observed by Sekiya (2006), who found that participants consistently displayed better tracking performance on the first random segment of the waveform than on the second random segment. Sekiya postulated that degraded concentration across a tracking trial might explain this finding.…”
Section: Introductionmentioning
confidence: 99%
“…While human movement and locomotion has many modes, almost all tasks rely on some form of postural stability (Skelton, 2001;Van Ooteghem et al, 2008). Maintaining balanced erect posture, contrary to appearances, is a very complex and dynamic process (Morningstar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%